ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PERILAKU WAJIB PAJAK UNTUK MENGGUNAKAN E-FILLING (Studi Kasus pada Wajib Pajak Kota Semarang) (Students' Journal of Accounting and Banking, 2014)
Online and real time internet base tax returns, it is called e-filing, have been launched since 2005 by Indonesia Directorate General of Taxes in order to improve quality of services to taxpayers. On it`s journey until present, e-filing is unpopular seen from the amount of it`s users. This research aims was to investigate the factors that influenced the behavioral intention taxpayers for using e-filling, particularly in Semarang. Data used in this researchis primary data by using questionaire and respondent is the Corporate Taxpayers who use e-filling in Semarang. Sample collection methods used in this research was convenience sampling or sampling which selection by easyer, the samples echievement is 95 respondents. The result of this research indicate that Security and Privacy and Readiness Technology Taxpayers Information significantly positive influence to behavioral intention for the efilling usage. Whereas, complexity significantly negative influence to behavioral intention for the e-filling usage.Keywords: E-filling, Security and Privacy, Complexity and Readiness Technology Taxpayers Information